MARKETING STRATEGIES AT BCA SYARIAH BANK IN INCREASING THE INTEREST OF THE MILLENNIAL GENERATION IN THE DIGITAL ERA - Kusuma Dewi, Ratna; Arfan, Kiagus (Prodi Magister Ekonomi Syariah FEBI UIN Raden Fatah Palembang, 2024)
BCA Syariah Bank's Marketing Strategy in Increasing the Interest of the Millennial Generation in the Digital Era provides opportunities and challenges for its existence. So Islamic banks must be able to use existing opportunities as best as possible, namely by improving marketing strategies in the digital era by embracing the millennial generation. The aim of this research is to determine the marketing strategy of Islamic banks in increasing the interest of the millennial generation in the digital era and also to determine the inhibiting factors in the marketing strategy carried out. The collection technique is through documentation. Data analysis using qualitative descriptive. The research results show that the marketing strategy of Islamic banks in increasing the interest of the millennial generation in the digital era can be done with a marketing mix strategy, namely creating a condition called bank less (banks without offices), the existence of product innovations that can attract the interest of millennials. namely marriage savings and sacrificial savings (one person one goat), digital banks are able to save costs because they are easy, simple and cheap, promotions by creating creative content competition activities, promotions involving influencers/clerics/artists and promotions involving an active role.